Apple Polyphenols Extract (APE) Alleviated Dextran Sulfate Sodium Induced Acute Ulcerative Colitis and Accompanying Neuroinflammation via Inhibition of Apoptosis and Pyroptosis - Fang Liu; Xinjing Wang; Yuan Cui; Yan Yin; Dong Qiu; Shilan Li; Xinli Li (Foods, 2021)
The main aim of this study was to investigate the potent anti-apoptosis and anti-pyroptosis effects of apple polyphenols extract (APE) on dextran sulfate sodium model group (DSS)-induced acute ulcerative colitis (UC) and the protective effect of APE against acute UC-related neuroinflammation and synapse damage. Forty-three C57BL/6 male mice were randomly divided into a control group (CON), a 3% DSS model group (DSS), a 500 mg/(kg·bw·d) APE group (HAP), and a 125 (LD) or 500 (HD) mg/(kg·bw·d) APE treatment concomitantly with DSS treatment group. The results showed that APE significantly ameliorated DSS-induced acute UC through inhibiting intestinal epithelial cell (IEC) apoptosis and the Caspase-1/Caspase-11-dependent pyroptosis pathway, with increased BCL-2 protein expression and decreased protein levels of NLRP3, ASC, Caspase-1/11, and GSDND. Furthermore, APE significantly reduced acute UC-related neuroinflammation and synapse damage, supported by decreased mRNA levels of hypothalamus Cox-2 and hippocampus Gfap and also increased the mRNA levels of hypothalamus Psd-95. The increased protein expression of ZO-1 and Occludin improved the intestinal barrier integrity and improved the function of goblet cells by upregulating the protein level of MUC-2 and TTF3 accounted for the beneficial effects of APE on UC-associated neuroinflammation. Therefore, APE might be a safe and effective agent for the management of acute UC.